2010
DOI: 10.1186/1479-5868-7-9
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a school-based physical activity-related injury prevention program on risk behavior and neuromotor fitness a cluster randomized controlled trial

Abstract: BackgroundTo investigate the effects of a school-based physical activity-related injury prevention program, called 'iPlay', on risk behavior and neuromotor fitness.MethodsIn this cluster randomized controlled trial 40 primary schools throughout the Netherlands were randomly assigned in an intervention (n = 20) or control group (n = 20). The study includes 2,210 children aged 10-12 years.The iPlay-intervention takes one school year and consists of a teacher manual, informative newsletters and posters, a website… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 19 publications
3
45
0
1
Order By: Relevance
“…Further training resulted in small non-significant improvements in neuromotor fitness in favor of the intervention group [44] . In addition, a substantial and relevant reduction in physical activity injuries (50%), especially in children of the low-activity group, was found [45] ( fig. 2 ).…”
Section: Importance Of Balance Trainingmentioning
confidence: 96%
See 3 more Smart Citations
“…Further training resulted in small non-significant improvements in neuromotor fitness in favor of the intervention group [44] . In addition, a substantial and relevant reduction in physical activity injuries (50%), especially in children of the low-activity group, was found [45] ( fig. 2 ).…”
Section: Importance Of Balance Trainingmentioning
confidence: 96%
“…Further, in a neurophysiologic approach, EMG responses to muscle stretch in the upper limb study were investigated in children. The results of this study indicated that long-latency EMG responses, probably involving supraspinal pathways, are already present at 2-3 years of age, but that the duration of these Development of static and dynamic balance across the life span (schematic illustration based on data from two studies [11,12]) and training-induced changes in balance performance (flow chart based on data from various studies [35,46,62,63]) and fall/injury reduction in children [45] and seniors [48,49]. Note: a range is presented when more than two studies were cited.…”
Section: Deficits In Postural Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…An American study evaluated the delivery of a Tai Chi group exercise programme to prevent falls in community dwelling older people through community health services 35. A Dutch school-based study evaluated the translatability and flexibility elements of a school-based programme aimed at preventing physical activity related injuries 36. An Australian study reported coaches' feedback on the implementation of a safe landings programme through targeted coach education sessions followed by coach delivery of the principles to their teams of junior netball players 37…”
Section: Conceptual Approaches For Intervention Development Deliverymentioning
confidence: 99%